DEVELOPMENT OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN SCIENTIFIC LIBRARY OF UEPA FOR EFFICIENT INFORMATIONAL AND BIBLIOGRAPHICAL SUPPORTING OF EDUCATIONAL AND SCIENTIFICAL PROCESSES IN THE ACADEMIES - Rybalchenko Olena М. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
This scientific research is devoted to constructive analysis of changes that have occurred and continue to occur in scientific library work as a result of information and communication technologies wide use.